1999
DOI: 10.1021/jp992518z
|View full text |Cite
|
Sign up to set email alerts
|

On the Vertical and Adiabatic Excitation Energies of the 2Ag State of trans-1,3-Butadiene

Abstract: The excitation energy to the 2 1 A g state of trans-1,3-butadiene is examined using a variety of ab initio electronic structure techniques. While analogous states have been shown to be the lowest singlet excited states for all longer polyenes, for butadiene the position of the 2 1 A g state relative to the HOMO f LUMO excitation (1 1 B u ) has been difficult to establish theoretically. We employ a variety of methods (CASSCF, CASPT2, MRSDCI, QDVPT) to examine both the vertical and adiabatic excitation energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 64 publications
4
25
0
1
Order By: Relevance
“…57,58 Rather, as shown by Aoyagi et al in octa-tetraene, 57 there is a lower dipole forbidden excitation, later identified as the 2A g − state, which can be rationalized in valence bond language as arising from a pair of singlettriplet excitations in the two separate double bonds that recouple to form a singlet state. [59][60][61][62][63][64][65][66][67] Following the observation of the 2A g − state in octa-tetraene, there has been much debate over the correct ordering of the 2A g − and 1B u + excited states in the shorter polyenes, compounded both by experimental difficulties in observing the dipole-forbidden 2A g − state as well as theoretical challenges in achieving a balanced description of the two states, which are dominated by very different kinds of correlation, namely, static correlation in the 2A g − state and dynamic correlation in the 1B u + state. In longer polyenes and the biologically active carotenoid and retinal pigments, questions about the low-lying spectrum are not restricted simply to the 2A g − and 1B u + state ordering.…”
Section: Introductionmentioning
confidence: 99%
“…57,58 Rather, as shown by Aoyagi et al in octa-tetraene, 57 there is a lower dipole forbidden excitation, later identified as the 2A g − state, which can be rationalized in valence bond language as arising from a pair of singlettriplet excitations in the two separate double bonds that recouple to form a singlet state. [59][60][61][62][63][64][65][66][67] Following the observation of the 2A g − state in octa-tetraene, there has been much debate over the correct ordering of the 2A g − and 1B u + excited states in the shorter polyenes, compounded both by experimental difficulties in observing the dipole-forbidden 2A g − state as well as theoretical challenges in achieving a balanced description of the two states, which are dominated by very different kinds of correlation, namely, static correlation in the 2A g − state and dynamic correlation in the 1B u + state. In longer polyenes and the biologically active carotenoid and retinal pigments, questions about the low-lying spectrum are not restricted simply to the 2A g − and 1B u + state ordering.…”
Section: Introductionmentioning
confidence: 99%
“…The low-lying electronic states of many conjugated molecules exhibit significant double excitation character in wave function treatments. 23,24,[27][28][29][30] A classic example is the family of polya͒ Electronic mail: nmaitra@hunter.cuny.edu enes. The lowest-lying singlet state of all polyenes is not a simple one-electron excitation from the highest occupied to the lowest unoccupied orbital of the ground state, but has a large zeroth-order contribution from a doubly excited determinant.…”
Section: Introductionmentioning
confidence: 99%
“…As a simple example, in linear polyenes, electron-electron interactions contribute to make the lowest excited singlet state ͑the 1 2A g state͒ one of double-excitation nature, rather than the singly excited highest occupied molecular orbital ͑HOMO͒ → lowest unoccupied molecular orbital ͑LUMO͒ state as one would expect in a single particle picture. [15][16][17] A more extreme example of this occurs in metallic nanotubes at low temperatures, where the qualitative electronic structure is believed to be of Luttinger liquid form. [18][19][20] Here we demonstrate that the density matrix renormalization group ͑DMRG͒, which we and others have recently been investigating in quantum chemistry, provides a solution to the question of how to flexibly and efficiently describe nondynamic correlation in systems that are large in one of their three spatial dimensions.…”
Section: Introductionmentioning
confidence: 99%